1994
DOI: 10.1021/ic00103a013
|View full text |Cite
|
Sign up to set email alerts
|

Preparations and X-ray Structures of Compounds Containing the Four-Membered PN2Te Ring

Abstract: The reaction of Li[Ph2P(NSiMe3)2] with TeCU in a 1:1 molar ratio in CH2CI2 at -78 °C, followed by warming to 23 °C, produces Pl^PCNSiMesUTeCU (1) in essentially quantitative yield. An X-ray analysis shows 1 to contain a four-membered PN2Te ring with Te-N bond distances of 2.056(3) and 2.185(3) Á. When the same reaction is carried out in a 2:1 molar ratio, the product is Ph2P(NSiMe3)2Te(Cl)NPPh2NSiMes (2), which consists of a PN2Te ring with Te-N bond distances of 2.108(3) and 2.275(4) Á and a short exocyclic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…31 The analogous tellurium diimides have been observed to undergo a facile [2+2] cycloaddition with the formation of thermally stable dimers RNTe(µ-NR)2TeNR. [34][35][36] A similar [2+2] cycloaddition has also been observed between Se(N t Bu)2 and t BuNSeO. 37 Sandblom et al 28 have reported a DFT study of the conformations and dimerization energies of E(NMe)2 (E = S, Se, Te).…”
Section: -32mentioning
confidence: 76%
“…31 The analogous tellurium diimides have been observed to undergo a facile [2+2] cycloaddition with the formation of thermally stable dimers RNTe(µ-NR)2TeNR. [34][35][36] A similar [2+2] cycloaddition has also been observed between Se(N t Bu)2 and t BuNSeO. 37 Sandblom et al 28 have reported a DFT study of the conformations and dimerization energies of E(NMe)2 (E = S, Se, Te).…”
Section: -32mentioning
confidence: 76%
“…Within this set, there are fifteen structures with Te-D SBIs shorter than 80% of the sum of r vdW (Table 2) and in each case the actual supramolecular synthon is the virtual four-membered heterocycle [Te-D] 2 . Six of these crystal structures (1,2,5-telluradiazole (32) [64], phenanthro(9,10-c)-1,2,5-telluradiazole (33) [65], 4,6-di-t-butylbenzo-2,1,3-telluradiazole (37) [44], benzo-2,1,3-telluradiazole (38) [66], 4,7-dibromobenzo-2,1,3-telluradiazole (39) [66], and the DMSO adduct of 4,7-dibromobenzo-2,1,3-telluradiazole (26) [66]) feature the synthon [Te-N] 2 assembled by 1,2,5-telluradiazole heterocyclic building blocks. The corresponding SBIs are very short; the same is observed for the SBIs in [Te D] (Table 1) formed by 1,2-tellurazole heterocycles, 6 [67] and 12 [54].…”
Section: [Te-m-d]mentioning
confidence: 99%
“…Hydrogen atoms have been omitted for clarity. Original data from Refs [40][41][42][43][44][45][46][47][48]…”
mentioning
confidence: 99%
“…Unexpectedly, an attempt to prepare a tellurium diimide by reaction II resulted in the formation of a benzotelluradiazole. The simplest method, III, is the reaction of an aromatic vicinal diamine with TeCl 4 [16]. In an early report [17] the attempted preparation of benzo-2,1,3-telluradiazole from o-phenylenediamine afforded a thermally unstable product; our own experiments identified this material as the result of incomplete deprotonation, C 6 H 4 (NH) 2 (TeCl 2 ), which was transformed by addition of an ancillary base into the desired compound in high yield.…”
Section: Synthesismentioning
confidence: 99%